Occurrence of Subclinical Endometritis in Dairy Cattle and Effect on Reproductive Efficiency - Vallejo, Dario; Chaves, Carlos; Benavides, Carmenza; Astaíza, Juan; Zambrano, Wilmer (Acta Scientiae Veterinariae, 2018)
Background: Subclinical endometritis (SE) have a negative impact on fertility due to an absence of clinical signs which difficult its diagnosis and treatment. The prevalence and impact of the disease on the reproductive status of dairy herds is not known in the region, the objective of the present study was to determine the prevalence of the disease and its effect on the reproductive efficiency in cows of the dairy area from Putumayo State, Colombia. Materials, Methods & Results: Cross-sectional study was made of 166 dairy cows from 30 days postpartum in the municipalities: Santiago, Sibundoy, Colon, and San Francisco. Reproductive evaluation and endometrial cytology were made to establish the SE prevalence determining subsequently the number of open days. Cow whit more than 120 days in milk (DIM) and without confirmed pregnancy was defined as “not reproductive efficiency”. Association between SE and reproductive efficiency was established through Odds Ratio from contingency tables. Bias and confusion control was made through stratified analysis. Results showed 32 cows without changes in reproductive clinical evaluation and inflammatory changes in cytological evaluation (PMNn >5%) for a SE prevalence of 19.27%. Disease occurs most frequently in Colón (23.10%) but the frequency of the disease was not different among the regions (P > 0.05). The group of animals with the greatest days open (DO) mean (161 DIM) had a normal ovarian function and subclinical endometritis. The 6.6% of cows had a poor reproductive prognosis (subclinical endometritis, anestrous and 144 DIM). For the stratified analysis (controlling by anestrus) was estimated the crude OR (OR 5.93; P < 0.05; CI 95% 2.56-14.6) and adjusted ORMH (OR 5.78; P < 0.05; CI 95% 2.39-13.9). Difference between adjusted ORMH and crude OR (3%) and Wald X2 test (P > 0.05) suggesting that there is no confusion and allowed to establish that “the odds of low reproductive efficiency (Days open >120) increases 5.9 times when cows suffer subclinical endometritis, than when do not have the disease”. Discussion: Study prevalence was lower than the reported by other authors. Variability of the results by the different authors ratifies the multifactorial characteristic of the disease and thr differences in the immune response of the animals. Cows diagnosed with SE, normal ovarian function and 161 DIM shown that the disease increases significantly the open days of the herd reducing reproductive efficiency. These findings are consistent with other authors who report that subclinical endometritis: increased open days and reduced conception rates and increased the risk of no pregnancy at 150 days postpartum. In the study, cows with subclinical endometritis and normal ovarian function had open days mean lower to 120 and more probability to have a good reproductive performance if pregnancy is achieved, but the dairy herds of the region lack of adequate systems of detection of estro and services and have no systems that allow the diagnosis of SE and anoestrus. The 69% of the evaluated animals present some clinical characteristics (SE, anoestrous) that predispose them to low reproductive behaviour. It is recommended to routinely use endometrial cytology to diagnose SE and improving the reproductive efficiency of animals.